Factors influencing community acceptability of mass drug administration for the elimination of onchocerciasis in the Asante Akim South Municipal, Ghana. - Emmanuel Kumah; Patrick Owusu; Godfred Otchere; Samuel E Ankomah; Adam Fusheini; Collins Kokuro; Frederick Mensah-Acheampong; Joseph Amankwah Atta; Samuel Kofi Agyei (Public Library of Science (PLoS), 2023)
Introduction Onchocerciasis is one of the eleven neglected tropical diseases (NTDs) recently targeted by the World Health Organization (WHO) for elimination. Mass drug administration (MDA) of ivermectin has become the main intervention for reducing the burden of onchocerciasis and controlling its transmission. However, despite the considerable gains in the fight against onchocerciasis in Ghana, the infection remains endemic in some communities. This study aimed to ascertain community members' acceptability levels and factors associated with ivermectin MDA for the elimination of onchocerciasis in the Asante Akim South Municipal in the Ashanti Region of Ghana. Methods A cross-sectional, questionnaire-based study was conducted in six communities in the Asante Akim South Municipal from 7th May to 9th July, 2021. The study population comprised all persons aged 18 years and above who had lived in the study communities for more than three months prior to the study. The main outcome variable was the acceptability of ivermectin MDA by the community members. This was measured using a composite acceptability score adapted from the Intervention Rating Profile tool. The explanatory variables were the respondents' socio-demographic characteristics, self-rated knowledge of onchocerciasis, perceived side effects of ivermectin, and self-reported level of education received on MDA activities. Results Out of 450 community members included in the study, 50.4% were male while 49.6% were female. The respondents' mean age was 39.57±10.64 years. The mean acceptability score for ivermectin MDA was 20.52±2.91 (range, 9-36). Acceptability of ivermectin MDA was positively associated with gender, educational status, employment status, self-rated knowledge of onchocerciasis, and level of education received on MDA; and negatively associated with perceived side effect of ivermectin. Conclusion This study provides valuable information to inform policy decisions on planning and implementing MDA programs for the elimination of onchocerciasis in the study area and the country as a whole.